THE CONFRONTATION OF IDEAS ON ROMANIAN ECONOMIC DEVELOPMENT BETWEEN THEWORLD WARS - Mariana, BUICAN (Strategii Manageriale)
The Great Union of 1918 led to the creation of a new economic body able to respond to new requirements of the Romanian society. The period between the two world wars is considered a development stage broad of the domestic economy. A role in this process had economic policy implemented by the authorities. This was based on the new economic doctrines that faced with stake Romanian economy development. Interwar economic trends were: liberalism - neoliberalism, national - peasantism and socialism.